Neurogenic stunned myocardium associated with pediatric brain tumor may not be catecholamine-induced - Shigeta Moriya (Annals of Pediatric Cardiology, 2015)
A rare case of pediatric neurogenic stunned myocardium (NSM) associated with a brain tumor is reported. A previously healthy 6-year-old boy presented with coma, and imaging studies revealed a brain tumor. On hospitalization day 3, he developed NSM and neurogenic pulmonary edema necessitating intensive cardiopulmonary support. Although blood marker levels of cardiac injury were elevated, his plasma and urinary norepinephrine levels were within normal limits. His cardiorespiratory functions markedly improved by hospitalization day 8. This case report may be one of the first to document plasma and urinary catecholamine levels in pediatric NSM. While solid conclusion cannot be drawn based on experience from a single case, these results suggest that pediatric NSM may not be catecholamine-induced.